Retreating rights: Human rights, pre-theoretical praxes and student activism in South African universities - Keet, A.; Nel, W.; Sattarzadeh, S. (South African Journal of Higher Education, 2017)
This paper is a recognition-theoretical reading of a research-study on pre-theoretical understandings of human rights amongst university students as ways to logically anchor agential options for student social activism. The study shows that the expected legal and political constructions of human rights are discursively dominant. However, from the overall results of the study, it appears students have more complex pre-theoretical understandings of human rights from which they derive justice-orientations as sources for activism. We conclude this has deliberative implications for human rights praxes.